Pictorial Depiction of an Institutional Experience of Acute Abdominal Emergencies in Cancer Patients with COVID-19 Infection - Ankush Jajodia; Anuraag Jena; Sunil Pasricha; Shaifali Goel; Gurudutt Gupta; Sunil Puri (Thieme Medical and Scientific Publishers Pvt. Ltd., 2022)
The ongoing pandemic of coronavirus disease 2019 (COVID-19) poses a diagnostic and management challenge to the clinician, which further gets heightened when patients present with abdominal complications in a cancer care center. The atypical manifestations of the disease provide a diagnostic conundrum to the radiologist and leave the pathologist in the perils of guiding further management to the clinician. Although previous literature shows gastrointestinal involvement in COVID-19, we present a case series of complicated subjects with clinical imaging as a pictorial essay and relevant pathology. The abdominal manifestations of COVID-19 are complicated in cancer patients where a variety of other differentials such as infiltration by metastatic disease and drug-related chemo toxicity effects must be taken into account, which may be ruled out by clinical workup, adequate imaging, and laboratory tests. This would help achieve better clinical acumen and modify management in these subjects.